KONFLIK DAN INTEGRASI (STUDI TERHADAP PENGEMBANGAN BUDAYA DAN KEARIFAN LOKAL DI KECAMATAN LEMPUING DAN LEMPUING JAYA) - Hamidah Hamidah; Siti Afiqah Bt Mohamed Tahir (Wardah, 2018)
The Study of Conflict and Integration (Study on Cultural Development and Local Wisdom in Lempuing and Lempuing Jaya Subdistricts) is a qualitative research with analytical descriptive research type using Sociological Approach, Historical Approach and Ethnological Approach. Some concepts that can be recorded are "pumpungan / pompong balong" (the concept of the community of Sungai Pinang Ogan Ilir), derived from the word "tampung", the collection of community donations, Sakai (the concept of Komering community) which means debt, Saoh (the concept of Sukaraja community ) which means support, hutangan, enjukan the concept of Sri Bandung community OI and "behantat" delivery to the community Sriguna. The concepts have been institutionalized into social behavior, which is a solid norm in regulating cooperation among citizens. All local wisdom is understood, applied, taught and passed down from generation to generation so as to create a set of attitudinal patterns in the daily life of mankind, between them and towards nature and its creator. Keywords: Lempuing, Lempuing Jaya, local wisdom